2001
DOI: 10.1080/02664760120076616
|View full text |Cite
|
Sign up to set email alerts
|

Estimators for a Poisson parameter using ranked set sampling

Abstract: Using ranked set sampling, a viable BLUE estimator is obtained for estimating the mean of a Poisson distribution. Its properties, such as efficiency relative to the ranked set sample mean and to the maximum likelihood estimator, have been calculated for different sample sizes and values of the Poisson parameter. The estimator (termed the normal modified r.s.s. estimator is more efficient than both the ranked set sample mean and the MLE. It is recommended as a reasonable estimator of the Poisson mean ( u ) to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…One exception is a paper by Barnett and Barreto (2001) who use the RSS methodology to estimate a Poisson parameter. In a more recent paper Lacayo et al (2002) discuss a RSS proportion estimator.…”
Section: Introductionmentioning
confidence: 97%
“…One exception is a paper by Barnett and Barreto (2001) who use the RSS methodology to estimate a Poisson parameter. In a more recent paper Lacayo et al (2002) discuss a RSS proportion estimator.…”
Section: Introductionmentioning
confidence: 97%
“…Nevertheless, some results pertaining to discrete random variables are beginning to emerge. For example, Barnett and Barreto [11] have successfully applied RSS to the estimation of Poisson parameters. Furthermore, Terpstra and Nelson [12] have shown that RSS can e ectively be used to estimate population proportions.…”
Section: Introductionmentioning
confidence: 99%
“…The unbiased linear estimator for the Poisson process mean using RSS data can be written as (cf. Barnett and Barreto) μtrue^RSS0.25emj=γnntruetrue∑i=1nX()i:nj, where γn=()1true/ntruetrue∑i=1nγi:n is correction constant chosen to minimize normalVnormalanormalr()trueμ^RSSj, the variance of i th order statistic for the i th sample of a subgroup size n . In this study, γ n is found to be approximately unity, γ n ≈ 1.…”
Section: Designing Poisson Ewma Control Chartsmentioning
confidence: 99%
“…In this study, γ n is found to be approximately unity, γ n ≈ 1. Barnett and Barreto defined the minimum variance of μtrue^RSS as normalVnormalanormalr()trueμ^RSS=λ0.25em()truetrue∑i=1nαi:n2true/βi:n()truetrue∑i=1n1true/βi:n()truetrue∑i=1nαi:n2true/βi:ni=1nα()i:n/β()i:n2. where α ( i : n ) and β ( i : n ) are, respectively, the mean and variance of reduced ordered variables η()i:nj=()X()i:njμtrue/μ.…”
Section: Designing Poisson Ewma Control Chartsmentioning
confidence: 99%